Current advances in solar-blind photodetection technology: using Ga2O3 and AlGaN. Issue 5 (6th January 2022) - Varshney, Urvashi; Aggarwal, Neha; Gupta, Govind
Abstract : Recent advancements and applications of solar-blind ultraviolet photodetectors utilizing Ga2 O3 and AlGaN materials. Abstract : The rapid spread of the novel coronavirus disease (COVID-19) and emergence of different variants worldwide have caused a pandemic. With the sudden outbreak of this virus, ultraviolet-C (UV-C) sterilizing devices are significantly employed to destroy around 99% of these viruses. However, continuous exposure to UV-C may harm the environment and humans, leading to an increased risk of skin cancer, DNA damage, cataracts and many more severe health complications, which may result in another pandemic situation. Thus, it is highly necessary to monitor the intensity of UV-C exposure and limit the radiation in the environment. It is advisable to employ a highly sensitive solar-blind (SB) UV photodetector (PD) together with UV-C radiation devices. Among the various ultra-wide bandgap semiconductors, AlGaN and Ga2 O3 have emerged as the most suitable materials for application in solar-blind photodetection devices due to their high radiation hardness and high chemical and thermal stability. In lieu of exploring efficient SB UV detection systems, herein, we present a comprehensive review of the latest progress in solar-blind UV PDs based on the device architecture and the accompanying physical mechanisms. Further, the technical issues related to material synthesis and device fabrication, which limit the large-scale implementation of these detectors, are also addressed. Finally, a perspective for the future integration of these semiconducting materials with emerging two-dimensional materials towards highly sensitive SB detection devices is given.